2020
DOI: 10.1172/jci135536
|View full text |Cite
|
Sign up to set email alerts
|

p53/microRNA-214/ULK1 axis impairs renal tubular autophagy in diabetic kidney disease

Abstract: Dysregulation of autophagy in diabetic kidney disease (DKD) has been reported, but the underlying mechanism and its pathogenic role remain elusive. We show that autophagy was inhibited in DKD models and in human diabetic kidneys. Ablation of autophagy-related gene 7 (Atg7) from kidney proximal tubules led to autophagy deficiency and worse renal hypertrophy, tubular damage, inflammation, fibrosis, and albuminuria in diabetic mice, indicating a protective role of autophagy in DKD. Autophagy impairment in DKD was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 64 publications
2
95
0
Order By: Relevance
“…For example, within the individual cell populations we found that in the PDGFR-β + cells during late injury, there was substantial loss of enriched miR-143 and -145 and a significant increase in miR-199 and -214 ( Supplemental Figure 8 ). We and others have previously shown that miR-214 is involved in renal injury and fibrosis ( 1 , 26 28 ).…”
Section: Resultsmentioning
confidence: 91%
“…For example, within the individual cell populations we found that in the PDGFR-β + cells during late injury, there was substantial loss of enriched miR-143 and -145 and a significant increase in miR-199 and -214 ( Supplemental Figure 8 ). We and others have previously shown that miR-214 is involved in renal injury and fibrosis ( 1 , 26 28 ).…”
Section: Resultsmentioning
confidence: 91%
“…M2 macrophages ameliorate podocyte injury is related to miR-25-3p ( Huang et al, 2020 ). It is found that autophagy deficiency in diabetic mice increases macrophage infiltration in proximal tubules ( Ma et al, 2020 ), and the induction of miR-214 enhances the autophagy impairment, thus aggravating renal inflammation ( Li et al, 2011 ). MiR-214 in monocytes is upregulated by AGEs, which in turn impairs the expression of the phosphatase and tensin homolog (PTEN) and delays spontaneous apoptosis of monocytes ( Li et al, 2011 ).…”
Section: Dn and Epigenetic Modifications Involved In Inflammationmentioning
confidence: 99%
“…Focusing on this topic, in a recent publication in Journal of Clinical Investigation, Ma et al 3 reported that p53 accumulation in the proximal tubule of diabetic kidneys is linked to kidney hypertrophy and damage through microribonucleic acid (miR)-mediated autophagy defects. The authors confirmed that autophagosome formation was impaired in the proximal tubules of Akita mice, a type 1 diabetic model due to insulin gene mutation, and a streptozotocin-induced type 1 diabetic mouse model.…”
mentioning
confidence: 99%
“…p53 has been known to regulate autophagy in a two ways: (i) turning autophagy on; and (ii) turning autophagy off. As described, Ma et al 3 provided a novel pathomechanism in DKD through fusion of classical knowledge with novel molecular biology techniques, showing that p53 turns kidney tubular autophagy off and contributes to kidney damage in diabetes. However, at the same time, there are several limitations/questions in their findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation